Irish tweed - Greeley, Andrew M., 1928-2013 (Greeley, Andrew M., 1928-2013. Nuala Anne McGrail novels., 2009)
Nuala Anne McGrail, a fey, Irish-speaking woman blessed with the gift of second sight, and her daughter have taken up karate to fight off schoolyard bullies who are harassing the family, while their incredibly shy nanny, Julie, is courted by a new fellow.